Kefir protects the liver against high fructose corn syrup induced phosphodiesterase hyperactivity - Pektas, Mehmet Bilgehan; Aslan, Esra; Guzel, Hilal; Korkmaz, Omer Adil; Celegen, Kubra; Pektas, Ayhan; Bostanci, Aykut; Sadi, Gokhan (WALTER DE GRUYTER GMBH, 2022)
Objectives Phosphodiesterases (PDEs) mediate several physiological activities, and alterations in PDE expressions might cause conflicts between functional and clinical effects. This study clarifies the eventual relationship between the hepatic insulin resistance-associated signaling elements and PDEs together with inflammatory markers and investigates the role of kefir in the treatment. Methods Male Wistar rats were grouped as Control, Kefir, HFCS (high-fructose corn syrup), and HFCS + Kefir. Daily HFCS (20% w/v) and kefir (1 mL/100 g weight) were given for 8-weeks. Hepatic expressions of PDE isoforms and insulin signaling elements were determined with qPCR and Western blot. The changes in hepatic phospholipase A2 (cPLA2) and insulin-like growth factor 1 receptor-alpha (IGF-1R alpha) were investigated histologically. Results HFCS upregulated hepatic PDEs while repressed primary insulin signaling elements at gene and protein levels. It also augmented cPLA2 and IGF-1R alpha expression. Kefir suppressed the PDEs and normalized the insulin signaling, and down-regulated cPLA2 and IGF-1R alpha in the liver of HFCS-fed rats. Conclusions The disruption of the insulin signaling pathway and activation of PDEs were negatively correlated in liver tissues of the HFCS-fed rats. Kefir treatment achieved a remarkable improvement in HFCS-dependent modifications, and it could be an excellent functional food against HFCS-induced insulin resistance, PDE hyperactivity, and inflammation.
Keywords: HFCS; inflammation; insulin signaling pathway; kefir; phosphodiesterase; 3B GENE-EXPRESSION; INSULIN-RESISTANCE; ADIPOSE-TISSUE; CAMP; INHIBITORS; DYSFUNCTION; SECRETION; Biochemistry & Molecular Biology